MODEL QFD DAN IPA 2 DIMENSI PADA PELAYANAN PASIEN COVID-19 DI RSDC WISMA ATLET DKI JAKARTA GUNA MENINGKATKAN KUALITAS LAYANAN KESEHATAN - Wilujeng, Fuji Rahayu; Rembulan, Glisina Dwinoor (Infotech: Journal of Technology Information, 2022)
Covid-19 (Corova Virus Disease 2019) is a type of infectious disease that is currently becoming a lot of conversation and causing concern for the public. Since the emergence of the first Covid-19 case, it has caused a stir that has occurred in various parts of the world, including Indonesia. Because Covid-19 can infect anyone without any age limit. Covid-19 also has an impact on a country's economic growth and losses in terms of public health.Another bad impact in terms of public health can be seen in the number of referral hospitals and emergency hospitals appearing based on government decisions. One of the emergency hospitals for Covid patients is the Wisma Atlet Covid-19 Emergency Handling Hospital (RSDC). Wisma Athlete's Wisma Atlet Emergency Hospital (RSDC), Kemayoran since its first operation on March 23, 2020 until now. The Covid-19 pandemic has resulted in a drastic increase in the various types of health services available. Therefore, the surrounding community certainly has hope for the quality of service in the available hospitals, especially the Wisma Atlet RSDC in order to meet user satisfaction. Based on the explanation above, this research was conducted which aims and is useful to find out what attributes are experiencing problems in the quality of service at the Wisma Atlet Hospital and find out the steps to improve the attributes that are experiencing problems. The method used in this research is Importance Performance Analysis 2 Dimension (IPA) which is used to measure service performance on the quality of service received by consumers based on the size of the assessment on reality and expectations, then followed by the Quality Function Deployment method used to provide technical responses sourced from Voice of Customer (VOC) so that it is hoped that in the future the RSDC Wisma Atlet can improve the quality of its services to improve public health.